2017
DOI: 10.3390/en10040534
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Input-Output Based Method to Estimate a National-Level Energy Return on Investment (EROI)

Abstract: Abstract:Concerns have been raised that declining energy return on energy investment (EROI) from fossil fuels, and low levels of EROI for alternative energy sources, could constrain the ability of national economies to continue to deliver economic growth and improvements in social wellbeing while undertaking a low-carbon transition. However, in order to test these concerns on a national scale, there is a conceptual and methodological gap in relation to calculating a national-level EROI and analysing its policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…The concept of EROI is part of the field of net energy analysis (NEA), and is one way of measuring and comparing the net energy availability from different energy sources and processes. In general, EROI can be defined as "the ratio between the energy returned from an energy-gathering activity compared to the embodied energy in that process" [55]. Although this concept was used initially to develop an energy-focused approach to the economy [56], the concept was adapted to calculate ratios between food energy output and food production energy inputs.…”
Section: Energy Return On Investment (Eroi)mentioning
confidence: 99%
“…The concept of EROI is part of the field of net energy analysis (NEA), and is one way of measuring and comparing the net energy availability from different energy sources and processes. In general, EROI can be defined as "the ratio between the energy returned from an energy-gathering activity compared to the embodied energy in that process" [55]. Although this concept was used initially to develop an energy-focused approach to the economy [56], the concept was adapted to calculate ratios between food energy output and food production energy inputs.…”
Section: Energy Return On Investment (Eroi)mentioning
confidence: 99%
“…The IEA documentation states that 'Energy industry own use contains the primary and secondary energy consumed by transformation industries for heating, pumping, traction, and lighting purposes, (including) for example, own use of energy in coal mines, own consumption in power plants and energy used for oil and gas extraction.' Some studies have used the EIOU to calculate EROI at a national level (e.g., Brand-Correa et al [114], King et al [115]), but the IEA metric only partly reflects the boundaries usually adopted for the EROI denominator [116]. In 2015, the IEA reported EIOU as 8.9% of total final global consumption ( [117], p. 47).…”
Section: A Proposed Net-energy Feedback Modelmentioning
confidence: 99%
“…In 1984, Cleveland et al [4] noted that the EROI value for a given energy source must be greater than 1:1 for its use to make sense in an economy; they also noted that fuels (or energy carriers) with higher EROI values play a greater economic role than do fuels (or energy carriers) with lower EROI values because of the importance of net fuel supply. Brand-Correa et al [5] calculated Some of these studies focused on the EROI ST analysis, while others studied a specific oil field or project. All these studies concluded that the EROI ST of China's fossil fuels is low and decreasing compared to those of most other nations.…”
Section: Introductionmentioning
confidence: 99%